Peran Platform Weverse Sebagai Sarana Interaksi Dan Ekonomi Dalam Industri K-Pop - Ciek Julyati Hisyam; Aline Nikita; Anissa Nurul Chotimah; Jemima Fathima Pasha; Nadila Sahla Mulia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Weverse is a platform launched by HYBE Corporation in 2019 and has played a central role in facilitating interactions between fans and artists in the Korean music industry (K-pop). Through exclusive access to content, direct communication with artists, and a membership system offering discounts and exclusive content, Weverse has become a